Signaling Crosstalks Drive Generation and Regeneration of the Thymus - Rosichini, Marco; Catanoso, Marialuigia; Screpanti, Isabella; Felli, Maria Pia; Locatelli, Franco; Velardi, Enrico (Frontiers in Immunology, 2022)
Optimal recovery of immune competence after periods of hematopoietic insults or stress is crucial to re-establish patient response to vaccines, pathogens and tumor antigens. This is particularly relevant for patients receiving high doses of chemotherapy or radiotherapy, who experience prolonged periods of lymphopenia, which can be associated with an increased risk of infections, malignant relapse, and adverse clinical outcome. While the thymus represents the primary organ responsible for the generation of a diverse pool of T cells, its function is profoundly impaired by a range of acute insults (including those caused by cytoreductive chemo/radiation therapy, infections and graft-versus-host disease) and by the chronic physiological deterioration associated with aging. Impaired thymic function increases the risk of infections and tumor antigen escape due to a restriction in T-cell receptor diversity and suboptimal immune response. Therapeutic approaches that can promote the renewal of the thymus have the potential to restore immune competence in patients. Previous work has documented the importance of the crosstalk between thymocytes and thymic epithelial cells in establishing correct architecture and function of thymic epithelium. This crosstalk is relevant not only during thymus organogenesis, but also to promote the recovery of its function after injuries. In this review, we will analyze the signals involved in the crosstalk between TECs and hematopoietic cells. We will focus in particular on how signals from T-cells can regulate TEC function and discuss the relevance of these pathways in restoring thymic function and T-cell immunity in experimental models, as well as in the clinical setting.